Kata hubung dan dan tetapi dari sudut pragmatik - Hasmidar Hassan (Kuala Lumpur : Dewan Bahasa dan Pustaka, 2011)
Conjunction in Malay language from pragmatic perspectives.
Includes bibliographical references (p. 181-198) and index.
In Malay.
Keywords: Malay language -- Conjunctions; Malay language -- Grammar; Malay language -- Usage